Description of the larvae and pupae of eight species of the tribe Sitonini Gistel, 1848 (Coleoptera, Curculionidae) from Central Europe - Gosik, Rafał; Sprick, Peter (Zootaxa, 2017)
Last instar larvae and pupae of Andrion regensteinense (Herbst, 1794), Charagmus gressorius (Fabricius, 1792), Sitona cylindricollis Fåhraeus, 1840, S. hispidulus (Fabricius, 1776), S. lineatus (Linnaeus, 1758), S. macularius (Marsham, 1802), S. obsoletus (Gmelin, 1790), and S. waterhousei Walton, 1846, are illustrated, re-described or described for the first time. Larval and pupal morphological diagnoses of the genera Andrion, Charagmus and Sitona as well as of the tribe Sitonini are updated and evaluated according to their utility for taxonomic studies. The assignment of the species to different development types is discussed.